Enterprise information planning – a new class of systems in information technologies of higher educational institutions of Ukraine - Teslia, Iurii; Yehorchenkova, Nataliia; Iegorchenkov, Oleksii; Kataieva, Yevhenia (Eastern-European Journal of Enterprise Technologies, 2016)
For the adaptation of the Ukrainian educational sphere to the realities of the modern world and the improvement in the education quality in Ukraine, the informatization of higher school is a necessity. The analysis of informatization of higher educational institutions of the western countries showed that the development of higher school is directed toward the creation of the united digital ecosystem with the common curricula, teaching staff and students. The studies, which will create conditions for uniting the information systems of institutes of higher education of Ukraine into this ecosystem, were carried out. The classification of the information systems of institutes of higher education was made and a three-component model (information technologies, actors and environment) was suggested. The analysis of the information exchange between these components was carried out. It was shown that the more actors are involved in providing information, the later it will be obtained by the end user and the higher probability of the error is. Therefore, it was proposed to develop information management system of an enterprise – Enterprise Information Planning (EIP), which can be used for informatization of institutes of higher education in Ukraine. The functions were developed and the EIP capabilities in the information management of an institute of higher education were determined. The method of reducing the time of processing requests to obtain the information based on planning the actors’ cooperation in EIP was proposed. Its essence lies in planning and controlling the actions of actors in the process of working with the information resource of EIP. The example of fulfilling requests to obtain the documents, which illustrates the advantage of the approach to informatization of an institute of higher education based on the EIP, was given. The algorithms, functions, the architecture and the interface of EIP were shown. The selection of a administrative superstructure over the means of information systems is their characteristic feature. The description of the EIP advantages and disadvantages was given. In particular, the possibility of localization of the information management functions IS should be distinguished. The disadvantages include additional expenditures of an institute of higher education for their creation. EIP makes it possible to solve information management problems at other enterprises, the work of which is connected with the need for managing considerable information resources.